Comparing Rural Adolescents from Farm and Nonfarm Families - Kimberly Esterman; Dalva Hedlund (Journal of Research in Rural Education, 1995)
This study explores the unique characteristics ofrural adolescents raised onfarms. Interpretive analyses suggest that farm adolescents are particularly close to their families and somewhat isolated from their peers and from peer-related activities. They are less likely than their nonfarm counterparts to plan on pursuing a 4-year college degree and are very unlikely to plan on remaining on the farm. Most felt that the influence of the farm was positive, resulting in an appreciation of and closeness with nature and animals, a sense of satisfaction and personal responsibility, and appreciation for the difficult work schedule and variety ofchallenges involved infarming. However, several participants identified limitations that resultedfrom their farm rearing, such as isolation from peers, a lack offree time, and difficulty pursuing outside interests. Implications for rural education are explored.